2012
DOI: 10.1007/s12565-012-0151-0
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of multi-detector computed tomography images before dissection may allow detection of vascular anomalies: a postmortem study of anomalous origin of the right subclavian artery and the right vertebral artery

Abstract: The Graduate School of Medicine at Chiba University is planning to introduce computed tomography (CT) images of donated cadavers to the gross anatomy laboratory. Here we describe an anomaly of the right subclavian artery that was detected by interpretation of CT images prior to dissection. The anomaly was verified to be the right subclavian artery, as the last branch of the aortic arch, by subsequent dissection of the cadaver. We also identified an anomalous origin of the right vertebral artery by dissection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…However, studies on such cases have often been reported (Hasebe, 1912;Adachi, 1928;Kasai, 1979). For example, Chiba et al (1981) summarized the findings in 94 of such cases reported in Japan and, recently, Sakamoto et al (2012) detected a case based on CT images before dissection, and they verified it on dissection. Developmentally, Barry's explanation (1951) has been widely accepted.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on such cases have often been reported (Hasebe, 1912;Adachi, 1928;Kasai, 1979). For example, Chiba et al (1981) summarized the findings in 94 of such cases reported in Japan and, recently, Sakamoto et al (2012) detected a case based on CT images before dissection, and they verified it on dissection. Developmentally, Barry's explanation (1951) has been widely accepted.…”
Section: Introductionmentioning
confidence: 99%